MENINGKATKAN KARAKTER RELIGIUS ANAK USIA 5-6 TAHUN MELALUI GERAK DAN LAGU - Nailah Amalia; Luluk Asmawati; Fahmi Fahmi (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
Religious Character in RA Idzotun Nasyiien Cakung East Jakarta is still low. This is based on the results of pre-research observation group B in RA. Idzotun Nasyiien who looks still low in devotion to God, loves others, and has good moral character or daily good behavior. Therefore this study aims to improve the religious character of group B children in RA Idzotun Nasyiien Cakung, East Jakarta. This research method is action research using the Kurt Lewin models. Cycle which consists of four phases: a) planning b) actions c) observations d) reflection. The study was conducted in January in the second semester of 2018. The process of collecting data is done through observation, field notes, interviews, and documentation. Data analysis was performed using quantitative and qualitative analysis. The results of the study showed that the analysis of activity increased in two cycles. In the first cycle it increased to 47% from the results of the pre-study observation of 28%. Then in cycle II it increased significantly from cycle I 47% to 80%. In the second cycle, the success criteria expected by researchers and collaborators were achieved.